Developing professional competence of a newly appointed head of a general secondary education institution in the context of advanced training - Vorobiova, N. (Problems of Engineer-Pedagogical Education, 2020)
Effective functioning of a general secondary education institution, effectiveness of innovations and implementation of education reforms, competitiveness of an education institution in the market of education services largely depend on the professionalism of its headmaster. Improving and updating legal support for this branch of the education system, granting autonomy to education institutions, expanding the range of responsibilities and roles of school principals as well as the existing difference in the level of training that candidates for the position demonstrate condition the need to update the system of advanced training and develop programs for newly appointed heads of schools based on the principles of differentiated and individualised approach to defining contents of educational courses. The result of such work must be aimed at developing professional competence of the heads of general secondary education institutions enabling them to effectively manage a modern educational institution in accordance with the requirements of the Concept of the New Ukrainian School. In the process of advanced training of newly appointed school principals, as in the course of any training, it is important to focus on the final result, which is not possible without systematic monitoring and mandatory evaluation of the effectiveness of each program individually, according to the defined criteria and indicators upon the completion of training. All this helps minimise the gap between the requirements for those who are applying for the position of the director of an education institution and their ability to exercise the powers assigned to them by local communities and the state. Only after understanding the shift in the perception of the concept of "advanced training" is it possible to update its content, forms, methods, instructional tools, and, therefore, its result, which is the acquisition of professional competences, with the aim of ensuring productivity and lasting development of general secondary education institutions. Ukraine's involvement into European integration processes is only possible if the education system is constantly improved. The driving force behind these processes should be professionally competent executives equipped with both theoretical and practical readiness for education management.